Measuring The Adoption of social media & Internet Technology for Retailing: An Analysis of Consumer Behaviour - Joydeep Mookerjee, Subir Chattopadhyay (Mathematical Statistician and Engineering Applications, 2022)
The widespread adoption of social media and internet technology has revolutionized how people interact, communicate, and access information. This research paper aims to measure consumers’ adoption of social media and internet technology by analyzing their behaviour towards these technologies. We conducted a quantitative study using a survey questionnaire to achieve this objective. The survey was administered to 86 participants, who were selected using a convenience sampling technique. The survey questionnaire consisted of questions related to demographic information, social media and internet usage behaviour, and factors that influence the adoption of these technologies. The study results indicate that adopting social media and internet technology among consumers is widespread, with most respondents reporting daily usage of these technologies. We found that the most significant factors influencing adoption are perceived usefulness, ease of use, social influence, and perceived enjoyment. Additionally, we found that the frequency of use of these technologies is positively associated with their adoption. Our research provides insights into consumer behaviour towards social media and internet technology adoption and highlights the importance of perceived usefulness and ease of use. The results of this study can be used by businesses and organizations to develop effective strategies for promoting and encouraging the adoption of social media and internet technology among their target audience.